The association between force-velocity profiles and the parameters from the 3-min all-out running test in university level soccer players - Sutcliffe, D. P.; Kramer, M. (Sport Sciences for Health, 2025)
Purpose This study aimed to explore the relationship between force-velocity (FV) profiles and parameters obtained from the 3-min all-out running test (3MT) to uncover essential connections for enhancing athletic training methodologies in university-level male soccer players.